The technologized investor : innovation through reorientation - Monk, Ashby H. B. (Ashby Henry Benning), 1976-; Rook, Dane, 1986- (Stanford Business Books, an imprint of Stanford University Press, 2020)
"Organizational and regulatory norms have long compelled investors to rely on others to innovate for them, which has diluted the quality of innovations as well as the power investors wield relative to the intermediaries. As machine intelligence advances, both in accessibility and sophistication, data is becoming an invaluable resource for businesses to mine as they seek to gain a deeper and more fluid understanding of their organizations and the world around them. Ashby Monk and Dane Rook urge large institutional investors, tasked with managing the majority of investable capital worldwide, to see this resource as the key to transformative innovation for growing the vast amounts of capital under their care"--